PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN SAINTIFIK PADA MATERI PEMANASAN GLOBAL - Diana Nur Nadiya Fitriya; Nur kuswanti; Oktaffi Arinna Manasikana (Discovery : Jurnal Ilmu Pengetahuan, 2021)
This research was conducted based on the science learning process which is still centered on the teacher (teacher center) and is still fixated on textbooks, so it requires learning resources in the form of LKPD. The purpose of this study was to determine the feasibility of student worksheets developed based on the validity of the LKPD based on the scientificoapproach. The type of research used in this researchiis developmentjresearchjusing thejADDIE developmentpmodel whichjconsists of several stagesk namely, Analysis,iDesign, Development, Implementation,iand Evaluation.oHowever, the implementation stage could not be implemented due to the covid 19 pandemic. The subjects ofithis studyiconsisted of experts (material experts and validation experts). The expert provides an assessment of the validity level of the LKPD basedpon the scientificoapproach developed by the researcher. Basedpon theiresults ofithe validators, validation results obtained based on the assessment of two validation experts and one material expert with an average score of 3.45% and 3.43% with the Very Valid category as LKPD on global warming material. Thus , the developed LKPD has met the eligibility criteria.